COVID‐19: The future of nursing will determine the fate of our health services. (23rd April 2021) - Catton, Howard
Abstract: Preparing the world to manage future pandemics must take priority. It is clear that we were not prepared for the COVID‐19 pandemic which continues to cause great suffering around the world. Nurses and other health professionals everywhere must be involved in health policy planning and implementation of public health measures to combat this and future pandemics. Such preparation needs community policy involvement at grassroots levels and needs to be collaboratively instigated at international levels. The death so far of over 2000 nurses is unacceptable in this pandemic, and we need to better protect and sustain the workforce. The International Council of Nurses has been instrumental in data gathering of nurses' experiences during COVID‐19. Key points from analysis of this data have been included in Second Progress Report of the World Health Organization's Independent Panel for Pandemic Preparedness and Response. This paper summarises the key messages from this report, as well as the nursing shortage. The International Council of Nurses resounds the call for massive investment in nursing education, leadership and jobs, as well as protection for our nurses on the frontlines of the pandemic.